Dampak Hoax Terhadap Ketahanan Nasional - Silvi Savira; Suci Ramadani Nasution; Saiful Saiful (Jurnal Pengetahuan Sosial dan Sejarah, 2026)
This study discusses the impact of the spread of hoaxes on Indonesia's national resilience, especially in the social, political, health, and economic contexts. The main issue raised is the increasing spread of hoaxes in the digital era, especially through social media, and its impact on national stability. This phenomenon is becoming more serious with the low digital literacy of the Indonesian people, which makes it easy for hoaxes to spread widely without verification of their truth. The main objective of this study is to see the extent to which hoaxes affect Indonesia's national resilience and to identify effective strategies in minimizing the threat of disinformation. Using a qualitative approach, data was obtained from various secondary sources such as reports from the Ministry of Communication and Information, Mafindo, and previous academic studies. Researchers analyzed the pattern of hoax spread through social media such as Facebook and WhatsApp. The main findings show that hoaxes contribute to decreasing public trust in the government, exacerbating political polarization, and triggering social unrest. In the health sector, hoaxes related to Covid-19  cause  fear  and  reduce  the  effectiveness  of  the  vaccination  program.  In  the economic sector. This study highlights the importance of increasing digital literacy and collaboration between the government and social media platforms to shape the flow of disinformation that threatens national resilience.